THE NUMERICAL SIMULATION OF THE BUFFETING'S APPEARANCE FOR ONERA M6 WING - I. I. Lipatov; P. T. Vinh (Научный вестник МГТУ ГА)
Introduction to the results of a numerical study buffeting on Onera M6 wing. The determination of condition to appear buffeting of the modes of oscillation of a shock when interacting with in the boundary layer at Mach numbers and angles of attack.